PLANNING BUSINESS PROCESS REENGINEERING (BPR) IN ACADEMIC LIBRARIES - Maharana, Bulu; Chandra Panda, Krushna (Malaysian Journal of Library and Information Science, 2001)
Academic libraries have always been playing a vital role in supporting the teaching, research and several other academic activities of its parent organization. However, these institutions are now facing organizational stress owing to the vast increase in number of publications, especially serials, in various formats, advances in information technology and increase in the propensity to consume information by academic community. The current situation necessitates the academic libraries to reengineer their traditional tools and work processes in order to make them more productive and effective. Business Process Re-engineering (BPR) has successfully been experimented in the business world for the revitalization of the organization. The proper planning and implementation of BPR in "the core processes" of the library would eliminate duplication and unnecessary steps, which add no value to library processes, improve user satisfaction, minimize cost and deliver quality services. The practical aspects of planning BPR from the perspective of academic libraries is discussed. The case studies highlighted the experiences with BPR as part of a strategic change in the management of academic libraries.